2000
DOI: 10.1063/1.372126
|View full text |Cite
|
Sign up to set email alerts
|

50 T pulsed magnetic fields in microcoils

Abstract: In this article we present a system based on microcoils capable of generating pulsed magnetic fields up to 50 T. We discuss the current generation and the measurement techniques currently used. We have measured the Faraday rotation for different paramagnetic materials, glass, gadolinium gallium garnet, Pr gallium garnet, and Si and have used the results to calibrate the magnetic field achieved. We discuss the relative merits of such a system compared to conventional ones, as well as the field characteristics o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 11 publications
0
31
0
Order By: Relevance
“…Because of the magnetic field inhomogeneity in such a large sample, its optimal volume should be limited to tens of mm 3 . It is not a serious limitation too, because we know of cases of research in high magnetic fields samples even of several µm 3 [15]. The research of small-sized samples is consistent with a current need of miniaturization in electronics and nanotechnology.…”
Section: Discussion Of Resultsmentioning
confidence: 75%
“…Because of the magnetic field inhomogeneity in such a large sample, its optimal volume should be limited to tens of mm 3 . It is not a serious limitation too, because we know of cases of research in high magnetic fields samples even of several µm 3 [15]. The research of small-sized samples is consistent with a current need of miniaturization in electronics and nanotechnology.…”
Section: Discussion Of Resultsmentioning
confidence: 75%
“…Moreover the possibility of latching leads to the fact that only a pulse of force is necessary to switch from one stable to another stable position. For such systems a pulse of current is sufficient and for evident thermal reasons, the possible current density achievable for such a pulse current, and so the forces, can be much higher than for a DC system [31].…”
Section: Advantages Of Electromagnetic Actuation and Down Scalingmentioning
confidence: 99%
“…The coil dimensions are of order of 100 m, and strong pulsed fields can be obtained with a total energy of less than 1 J. In fact, Mackay et al 5 successfully generated 50 T in such a microcoil, and suggested the use in magneto-optic experiments such as Faraday rotation.…”
mentioning
confidence: 98%